Políticas de salvamento e risco bancário em período de crise - Vilarins, Ramon Silva (2016)
This dissertation analyzes the impact of government bailout policies on the risk of the banking sector in OECD countries between 2005 and 2013. First, in line with the moral hazard hypothesis, I verify that financial institutions with high bailout expectations assume higher risks than others. Second, I find that, in normal times, rescue guarantees to large financial institutions distort competition in the sector and increase the risk of the other institutions. However, during the recent financial crisis, increases in the rescue expectation of competitors of an institution, to the extent that they represent a reduction in its chance of bailout, decrease its risk taking. Additionally, in a crisis period, I find that the deterioration in the countries’ sovereign capacity to bailout banks is associated with lower risk taking; on average, i.e., the increase in risk taking is higher in countries with a lower credit default swap spread.